Grapevine salt tolerance. (25th March 2021) - Zhou‐Tsang, A.; Wu, Y.; Henderson, S.W.; Walker, A.R.; Borneman, A.R.; Walker, R.R.; Gilliham, M.
Abstract: Salinity, which is predominantly an issue for agricultural systems in arid and semi‐arid regions, has the potential to impair grape production and wine quality, and its impact on the grape and wine industries is predicted to increase with climate change. Research on the physiological and molecular changes that occur in salt‐affected vines has unveiled complex osmotic and ionic responses that include oxidative stress, water loss, photoinhibition, growth inhibition and necrosis. Proposed salt tolerance mechanisms include elevated antioxidant production, hydric regulation and salt exclusion from shoots and berries. These later of these mechanisms is found in certain Vitis genotypes that, when grafted as rootstocks, can protect fruit‐bearing scions from accumulating significant amounts of saline ions from soils, most notably through the presence of specific transport proteins that are involved in regulating the transfer of ions from root to shoot via the xylem. Significant gaps in knowledge remain, however, regarding salt tolerance mechanisms for Vitis species, with many mechanisms inferred from other species or documented only at the level of gene expression. A better understanding of the mechanisms that confer salt tolerance in Vitis species is needed to improve the production of new germplasm that is locally adapted and better suited to the challenges of a changing climate. Hence, this review covers the current knowledge on the characteristics that are associated with salt damage and tolerance in grapevine cultivars and rootstocks and highlights possible future avenues that will enable development of new options for the industry to combat salinity.